2022
DOI: 10.3389/fendo.2021.833474
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Revealed the Pharmacodynamic Network of Bugu Shengsui Decoction Promoting Osteoblast Proliferation

Abstract: Background and ObjectiveWith high morbidity and disability, osteoporosis is a worldwide bone metabolism disease, regulated by complex pathological processes. Insufficient osteogenesis is greatly essential to osteoporosis. Traditional Chinese Medicine, a complex natural herbal medicine system, has increasingly attracted attention all over the world. Bugu Shengsui Decoction, a compound formula for osteoporosis, has significant clinical effects in the treatment of osteoporosis. Yet the detailed mechanisms are unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Metabolomics combined with proteomics analysis of femur provided a comprehensive interpretation of the changes in PMOP under salidroside treatment [135]. Furthermore, a study investigating the mechanism of action of Bugu Shengsui Decoction in treating osteoporosis revealed that the decoction promotes osteogenesis via the PI3K-AKT pathway, highlighting its potential as a therapeutic target for osteoporosis [136]. By targeting these dysregulated proteins and pathways, novel therapeutic interventions can be developed to restore bone homeostasis and prevent fractures in osteoporotic patients.…”
Section: Proteomic Identification Of Novel Therapeutic Targetsmentioning
confidence: 99%
“…Metabolomics combined with proteomics analysis of femur provided a comprehensive interpretation of the changes in PMOP under salidroside treatment [135]. Furthermore, a study investigating the mechanism of action of Bugu Shengsui Decoction in treating osteoporosis revealed that the decoction promotes osteogenesis via the PI3K-AKT pathway, highlighting its potential as a therapeutic target for osteoporosis [136]. By targeting these dysregulated proteins and pathways, novel therapeutic interventions can be developed to restore bone homeostasis and prevent fractures in osteoporotic patients.…”
Section: Proteomic Identification Of Novel Therapeutic Targetsmentioning
confidence: 99%
“…Metabolomics combined with proteomics analysis of the femur provided a comprehensive interpretation of the changes in PMOP under salidroside treatment [140]. Furthermore, a study investigating the mechanism of action of Bugu Shengsui Decoction in treating osteoporosis revealed that the decoction promotes osteogenesis via the PI3K-AKT pathway, highlighting its potential as a therapeutic target for osteoporosis [141]. By targeting these dysregulated proteins and pathways, novel therapeutic interventions can be developed to restore bone homeostasis and prevent fractures in osteoporotic patients.…”
Section: Proteomic Identification Of Novel Therapeutic Targetsmentioning
confidence: 99%